PENGARUH FRAKSI VOLUME FIBER SISAL (Agave sisalana) TERHADAP KEKUATAN FLEKSURAL RESIN KOMPOSIT - Eko Hadianto, Liftia Layyinatus Syifa, Helmi Fathurrahman Hanafie (Odonto : Dental Journal, 2018)
Background: Composite resin is filling material that used in dentistry fieldbecause of good aesthetic. Use of fiber as reinforced composite resin (FRC)begins to be developed because it has a lot of functions, such as increasestrength, stiffness, material hardness from fracture, and decrease shrinkage.Fiber composite resin has syntetic characteristic and needs chemical processalso has an expensive price. Therefore, natural fiber is easier to find, cheaper and can be developed as an alternative substitute of syntetic fiber. One of the natural alternative is sisal fiber. This study aims to know the effect of volume fraction of sisal fiber to composite resin flexural strength with sisal fiber concentration 1%, 2%, 3%, 4%.Method: This study was true experimental with post test only control groupdesign which divided into 4 groups RK+FS 1% (K1), RK+FS 2% (K2), RK+FS3% (K3), RK+FS 4% (K4). The data was analized using one way ANOVA assayand Post Hoc with significant degree 5%.Results: Mean of flexural strength sum K1=50,87 MPa, K2=42,96 MPa,K3=33,94 MPa, K4=24,32 MPa. Result of one way ANOVA assay showed valuep=0,000. Result of further assay Post Hoc showed K1 with K2 p=0,002, K1 withK3 p=0,000, K1 with K4 p=0,000, K2 with K3 p=0,001, K2 with K4 p=0,000, K3with K4 p=0,000.Conclusions: Concluded that there is good effect of sisal fiber volume fractionto composite resin flexural strength. Flexural strength RK+FS 1% has higherstrength than RK+FS 2%,3%,4%. Sisal fiber could become a natural fiberalternative in dentistry restoration material.